MANAJEMEN KEPALA SEKOLAH DALAM PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMP NEGERI DI KOTA BANDA ACEH - Ainul Fitri; Murniati .; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
The aim of this research was to figure out the principal’s management behavior in managing BOS fund at State Junior High Schools in Banda Aceh. This qualitative research was conducted by employing a descriptive method. The results showed that (1) the planning program was arranged at the b1eginning of each academic year by the school finance teams according to the results of discussions and meetings with the teachers, the members of school committee and the students’ parents. The results were written in the school work and budget planning by considering 8 educational system standards of Indonesia in order to decide the priority scales based on the available fund. In addition, (2) the implementation of this program began with coordination and socialization. Moreover, the implementation was in accordance with the technical guidance of BOS fund distributed by the Education Board of Banda Aceh Municipality. It was also found that (3) monitoring and was done by the teachers, members of school committee, the principals, the inspectorate, the team of BOS fund from each school, the municipality, and the province. The monitoring report was submitted to the Local Government Agency (SKPD) every three month period. Lastly, (4) the limitations, the delays, and the society’s misunderstanding related to BOS fund were the obstacles found in managing the BOS fund at the schools.Keywords: management, principal, school operational assistance (bos) fund